Psychometric evaluation of a brazilian portuguese version of the spitzer quality of life index in patients with low back pain Evaluación de las calidades psicométricas de una versión brasileña del spitzer quality of life index en pacientes con dolor lumbar Avaliação das qualidades psicométricas de uma versão brasileira do spitzer quality of life index em pacientes com dor lombar - Rafaela Cunha Matheus Rodrigues Toledo; Neusa Maria Costa Alexandre; Roberta Cunha Matheus Rodrigues (Universidade de São Paulo, 2008)
The purpose of this study was to adapt the Spitzer Quality of Life Index and evaluate its reliability in patients with low back pain. The following steps were followed: translation, back-translation, evaluation by a committee, and pretest. The reliability was estimated through stability and homogeneity assessment. The validity was tested comparing scores of the Spitzer (QLI) with the SF-36 and the Roland-Morris. The psychometric properties were evaluated by the self-application on 120 patients. Results showed that the Cronbach's Alpha was 0.77. Intraclass correlation coefficient for test-retest reliability was 0.960 (p<0.001; IC95%: 0.943; 0.972). Spearman´s correlation coefficient for test-retest reliability was 0.937 (p<0.001). There was significant correlation between the Spitzer (QLI) scores and the dimensions of the SF-36. A significant negative correlation was found between the Spitzer (QLI) and the Roland-Morris scores (r = - 0.730). The adaptation process was conducted successfully and the questionnaire presented reliable psychometric measures. Este estudio tuvo como objetivo realizar la adaptación cultural del Spitzer Quality of Life Index y evaluar su confiabilidad en pacientes portadores de dolor lumbar crónico. Se siguieron las siguientes etapas: traducción, retrotraducción, evaluación por un comité y pre-prueba. La validez fue obtenida por medio de la correlación entre los puntajes del Spitzer (QLI), del SF-36 y del Roland-Morris. Las propiedades psicométricas fueron evaluadas en 120 pacientes. Los resultados demostraron un coeficiente alfa de Cronbach=0,77. En una nueva pre-prueba, se encontró un coeficiente de correlación intraclases ICC=0,960 (p<0,001; IC95%: 0,943; 0,972). El coeficiente de correlación de Spearman fue de r=0,937 (p<0,001). Las correlaciones entre los puntajes del Spitzer (QLI) y de SF-36 fueron significativas. Correlación negativa entre los puntajes de Spitzer (QLI) y de Roland-Morris fue de (r= -0,730). El proceso de adaptación cultural fue realizado con suceso y la versión adaptada presenta medidas psicométricas confiables. Este estudo teve como objetivo realizar a adaptação cultural do Spitzer Quality of Life Index, e avaliar sua confiabilidade em pacientes portadores de dor lombar crônica. Foram seguidas as seguintes etapas: tradução, retro-tradução, avaliação por um comitê e pré-teste. A confiabilidade foi avaliada por meio da consistência interna e da estabilidade. A validade foi obtida por meio da correlação entre os escores do Spitzer (QLI), do SF-36 e do Roland-Morris. As propriedades psicométricas foram avaliadas em 120 pacientes. Os resultados demonstraram coeficiente alfa de Cronbach=0,77. No teste-reteste, encontrou-se coeficiente de correlação intraclasse ICC=0,960 (p<0,001; IC 95%: 0,943; 0,972). Coeficiente de correlação de Spearman foi de r=0,937 (p<0,001). As correlações entre os escores do Spitzer (QLI) e do SF-36 mostraram-se significativas. Observou-se correlação negativa significativa entre os escores do Spitzer (QLI) e do Roland-Morris (r= - 0,730). O processo de adaptação cultural foi realizado com sucesso e o questionário apresentou medidas psicométricas confiáveis.